Consumo de alcohol: impacto en el desarrollo cerebral del adolescente - Cepeda Rodríguez, Celso Enrique (2014)
This article goes in depth about subjectof alcohol consumption dangers overbrain formation when one is pubertal oradolescent and the consequences couldbe present in the medium term andthe long term for neuronal connectionsquality to be made.